2015
DOI: 10.1007/s10934-015-0025-7
|View full text |Cite
|
Sign up to set email alerts
|

Processing of silica bonded porous SiC preform for metallic composites

Abstract: Porous SiC ceramics were successfully fabricated by silica bonding of SiC compacts and porogen burnout technique. Silica coating on SiC particle was carried out using TEOS hydrolysis and crystallizes during the sintering process at 1200°C, which forms a well-developed neck growth between the SiC particles. Different volume fractions of sodium chloride porogen were used to obtain varied porosity content in porous SiC ceramics from 36 to 62.47 % leading to wide-ranging compressive strength from 8.11 to 0.69 MPa.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…reported that the flexural strength of porous silica‐bonded SiC ceramics prepared by infiltration method decreased from ∼47.9 to ∼29.5 MPa as the porosity increased from 26.1% to 35.6%. Many other researchers have also reported the same trend in porous silica‐bonded SiC ceramics 34,35,39–41 . In summary, the mechanical strength of porous SiC ceramics decreases with an increase in porosity. Effect of porosity on thermal conductivity: Kim et al 34 .…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…reported that the flexural strength of porous silica‐bonded SiC ceramics prepared by infiltration method decreased from ∼47.9 to ∼29.5 MPa as the porosity increased from 26.1% to 35.6%. Many other researchers have also reported the same trend in porous silica‐bonded SiC ceramics 34,35,39–41 . In summary, the mechanical strength of porous SiC ceramics decreases with an increase in porosity. Effect of porosity on thermal conductivity: Kim et al 34 .…”
Section: Introductionsupporting
confidence: 62%
“…One approach that provides economic advantages due to the application of low sintering temperature (<1450°C) while enhancing necking between SiC particles is the oxidation bonding technique 34–37 . The oxidation bonding method entails the preparation of an SiC powder‐template body followed by sintering the green body in air to promote bonding of SiC particles by in situ oxidation‐derived SiO 2 34–41 . SiO 2 as bonding phase provides a beneficial effect in reducing the temperature required to make necking between particles and facilitating partial densification of SiC strut 14,15,38,41 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, oxide bonding sintering attracts more and more attention because it enables porous SiC ceramics to be sintered at a temperature lower than 1600 ℃, which dramatically reduces the fabrication cost. The first oxide bonding phase studied is silica (SiO2) in the cristobalite phase and/or amorphous form at room temperature [7,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to the partial sintering and a tiny bit of oxide additions, the densification of sintered bodies is inadequate, and then pores are successfully formed [23]. Earlier studies about porous L-SiC ceramics have mostly focused on the types of additions such as silica [24,25], alumina [21], yttria [26], silicon nitride [27], mullite [28,29,30], glass frit, cordierite [31], CeO 2 [16], V 2 O 5 [32], and so on. They have summarized the effects of starting powders, additive amount, and sintering temperature on the microstructure of porous L-SiC ceramics, which were all prepared by pressureless sintering.…”
Section: Introductionmentioning
confidence: 99%